Tube model predictive control for a class of nonlinear discrete-time systems - Hashem Imani Marrani (Taylor & Francis Group, 2019)
This paper signifies a tube model predictive control for discrete time uncertain nonlinear systems in the presence of bounded disturbances. The problem of obtaining robustness against parametric uncertainty is renewed to the problem of grasping robustness against additional bounded disturbance. The nominal control law is achieved through the same computational burden as that of standard MPC with guaranteed stability. Also, ancillary control law is accomplished by H∞ control approach to stabilize the states despite parametric uncertainty and disturbances. A simulation example is exploited to show the effectiveness and applicability of the method.